An automated system for citation definition and publication. - Martin, Royceton. (2008)
This study reports on the design and development of an automatic system, AutoCite, to aid authors in the creation of citation information.Citation information is typically defined and used in the Bibliography or Reference section of a document to collate a list of all the materials that have been consulted during the preparation of the document.Although there are many citation authoring software that are available on the World Wide Web, they fall short in the capturing of data that is being cited, and also in combining the data is being cited with the document. This study attempts to derive a solution to these problems.This system was designed as an add-in to MS-Word 2000. This has been chosen since this is currently one of the most popular word processing software capturing over 80 percent market share of the market. The system was developed in Visual Basic for Applications (VBA) an object oriented programming language that is part of the suite of development tools in MS-Word 2000. This study attempts to derive a solution to exixting citation authoring software problems.